Prediction and diagnosis of sickling disorders in neonates. Issue 1 (January 1989) - Adjaye, N; Bain, B J; Steer, P
Abstract : A pilot scheme for the prediction and detection of sickle cell disease in neonates was set up and the results from its first three years of operation analysed. A total of 153 women booking at the antenatal clinic were found to have haemoglobin S. The protocol required that all partners of the women so identified be screened for abnormal haemoglobins and beta thalassaemia trait, and that the babies of these women should have cord blood electrophoresis performed. In fact this was only achieved in 75 partners (49%) and 91 of 145 infants (63%). Of 10 babies born with sickle cell disease during the study period, nine had mothers known to have haemoglobin S or C, but only four of these mothers' partners had been tested before delivery of the child. This pilot study highlights the problems in establishing effective antenatal screening programmes, especially in ethnic minority groups. The results show that detailed staff training, careful organisation of administrative arrangements, and education of 'at risk' groups should all be undertaken before the launching of major screening initiatives.